Читаем после букваря: [пособие для развивающего чтения] / Т. А. Ткаченко ; [иллюстрации Елены Мельниковой] - Ткаченко Татьяна Александровна (Эксмо, 2014)
Экземпляры: (20141106) / Инвентарный номер: 37914 / Цена: 167.00 / Сис.шифр: 74.102 / Авт.знак: Т 48 / ГРНТИ: 14 / ББК: 74.102